Calculation of Differential Cross Sections for Electron Impact Excitation of $H$ and $He^+$ (Journal of Atomic and Molecular Sciences, 2021)
We present the distorted wave Born approximation (DWBA) for electronimpact excitation and a method to calibrate the DWBA. With the calibrated DWBA, thedifferential cross sections (DCS) for excitation of $H$ and $He^+$ from 1s to 2s and 2p arecalculated and the results are compared with the absolute experimental measurementsfor $H$ at incident energies of 50 eV and 100 eV. It has been found that the theoreticalresults are in very good agreement with the experiment, which confirms the validityof the calibration procedure. This work prepares an efficient theoretical method fornumerical simulations of non-sequential double ionization of $He$ in strong laser pulsein which laser-induced electron impact excitation of $He^+$ is involved.
Keywords: electron impact excitation; distorted wave Born approximation; differential cross sections; total cross sections.